Production of Mycelium-Bound Lipase from Rhizomucor Miehei and its Application in the Modification of Palm Kernel Olein: Anhydrous Milk Fat for Ice Cream Emulsion - Liew, Margaret Yoon Bing (2001)
The production conditions and characteristics of mycelium-bound lipase (MBL) from Rhizomucor miehei, its catalytic performance in fat transesterification (TE) and the feasibility of using the enzyme to produce a transesterified fat suitable for use in ice cream formulation were investigated. The production of MBL was studied over a 5-day incubation period. Maximum dry mycelium weight and highest lipolytic activity were obtained after 3 days incubation in a medium containing 0.1% (w/v) glucose and 1.0% (w/v) palm olein. Production of MBL was demonstrated to be inducible where the addition of 0.5-5.0% (w/v) of palm oil resulted in a significantly (p..0.05) higher lipolytic activity than culture without any added oil. High levels (>0.5%) of glucose concentrations were found to inhibit the synthesis of MBL and insufficient lipase was produced to catalyse the TE reaction of palm stearin (POs) and palm kernel olein (PKOo) (1:1, w/w) mixture at 60°C. MBL was found to achieve optimum TE activity after 24 h reaction time and its catalytic stability was demonstrated following five repeated usage in TE reaction. Results obtained also illustrated the capability of MBL in transesterifying different oil substrates in a manner similar to that of Lipozyme 1M 60 (Novo Nordisk Industries, Copenhagen, Denmark), which is a commercial preparation of immobilised R. miehei lipase. Mixtures of PKOo:anhydrous milk fat (AMF) at different ratios (100:0, 70:30, 60:40,50:50 and 0:100, w/w) were transesterified using MBL in a solvent-free system. The triglyceride (TG) profile, slip melting point (SMP), solid fat content (SFC), melting thermogram and the polymorphic forms of the unreacted and trans esterified mixtures were evaluated. Results indicated that TE by MBL produced oil mixtures with new TG profiles, relatively lower slip melting points and solid fat contents. The melting thermo grams from differential scanning calorimetric analysis indicated an overall shift to lower melting TG. This study also demonstrated that the transesterified PKO₀:AMF mixture at 70:30 (w/w) ratio completely melted at 25°C which meets the melting criteria for fat used in ice cream formulation. AMF, unmodified PKO₀:AMF mixture (70:30, w/w) (control mixture) and transesterified PKO₀:AMF (70:30, w/w) were used in the preparation of ice cream emulsions. Results obtained show that emulsion prepared using TE-PKO₀:AMF (70:30,w/w) blend exhibited higher viscosity and greater strength than that of either AMF or unmodified PKO₀:AMF (70:30, w/w), which are amongst the desired properties of ice cream emulsion. This further support that TE of PKO₀:AMF (70:30, w/w) is capable of producing fat that is suitable for use in the preparation of ice cream emulsion.